(untitled) (Alberta Journal of Educational Research, 2015)
Through interviews conducted in the fall of 2013 and winter of 2014, this paper presents a portrait of the various issues faced by community activists in fighting to keep their small rural schools open amidst constraints, most notably, provincial budget cuts and low enrolment numbers in rural areas. At the same time, school board members seeking to close small schools in rural areas faced their own sets of constraints. Participants were asked to discuss: their experiences in the small schools review process, their suggestions for policy design and implementation, and their notions around what small schools mean to rural sustainability and future economic development. Throughout these interviews, the participants from both contexts highlighted the struggles they faced during the review process and the impact of school closures on their children, their communities, and themselves. In addition to metrocentric (Green & Corbett, 2013) assumptions faced by the activists in the school review and closure process, there were additional issues concerning the configurations of people with different orientations as they attempted to participate in a democratic dialogue within the school closure process. Cet article présente, par le biais d’entrevues ayant eu lieu à l’automne 2013 et l’hiver 2014, un aperçu des divers enjeux qu’affrontent les activistes communautaires dans leur lutte pour maintenir ouvertes leurs petites écoles rurales dans le contexte de contraintes, notamment les compressions budgétaires du gouvernement provincial et le faible nombre d’inscriptions dans les milieux ruraux. En contrepartie, les membres des conseils scolaires voulant fermer les petites écoles dans les milieux ruraux faisaient face à leurs propres contraintes. On a demandé aux participants de discuter des éléments suivants : leurs expériences lors du processus d’examen des petites écoles; leurs suggestions quant aux nouvelles politiques et à leur mise en œuvre; et leurs idées sur le rôle des petites écoles dans la durabilité rurale et le développement économique à l’avenir. Tout au long des entrevues, les participants des deux contextes ont souligné les luttes qu’ils ont affrontées pendant le processus d’examen, ainsi que l’impact des fermetures d’écoles sur leurs enfants, leurs communautés et eux-mêmes. Les participants ont évoqué, en plus des suppositions « métrocentriques » (Green & Corbett, 2013) auxquelles ont dû faire face les activistes pendant les processus d’examen et de fermeture, des enjeux impliquant les configurations de gens avec différentes orientations qui tentaient de participer au dialogue démocratique au sein du processus de fermeture des écoles.